Manganese dioxide/ reduced graphene oxide composite an electrode material for high-performance solid state supercapacitor. (10th March 2019) - Jadhav, Sarika; Kalubarme, Ramchandra S.; Terashima, Chiaki; Kale, Bharat B.; Godbole, Vijay; Fujishima, Akira; Gosavi, Suresh W.
Abstract: Transition metal oxides with many reversible oxidation states are normally considered as potential active materials for supercapacitor applications. The composite of graphene with MnO2 nanorods is obtained using hydrothermal oxidation of Mn-precursor on a graphene surface and tested as an electrode material in supercapacitor devices. In microstructural exploration, a fine distribution of MnO2 nanorods over the entire graphene surface is evinced by transmission electron microscopy. The galvanostatic charge-discharge performance of the composite electrode in a symmetric device formation displayed a high energy density of 42.7 Wh kg −1 corresponding to a specific capacitance of 759 F g −1 . This composite electrode material shows enhancement in the charge storage capacity by the factor of 2 and long life cycle with better retention of capacitance with small diffusion resistance. The excellent performance achieved for solid state supercapacitor device, in the present case, is attributed to the MnO2 /graphene composite structure, which not only provides the passage for the electrons but also increases the ion transportation during the fast charge-discharge reaction.